An analysis of the implications of the amendment of the section 10 (1)(0)(ii) foreign remuneration exemption from the perspective of the South African economy, global employer and expatriate - Swart, Johannes Petrus (My University, 2019)
The purpose of this report is to evaluate the amendment of the Foreign Remuneration Exemption contained in s 10(1)(o)(ii) of the South African Income Tax Act 58 of 1962 (the Act). This report firstly examines the history, definitions and concepts applicable to the relevant exemptions. South Africa has long been regarded as the starting point for investors to expand into Africa (la Grange, da Silva, Madden, Gouws, Duffy, van Wyk & de Villiers 2017:6). Therefore this report will examine the implications, resulting from the above mentioned amendment, on the South African economy, its taxpayers (employees) and employers. In addition, this report will be from a global mobility perspective therefore making reference to expatriates and global employers. As the Foreign Remuneration Exemption is not the only tax relief mechanism available to taxpayers, the report will also examine the other available tax relief mechanisms (for example double taxation treaties and foreign tax credits) and their implications. The ultimate purpose of this report will be to conclude, from a global mobility perspective, on whether the amendment to s 10(1)(o)(ii) will have a negative impact on global employers, expatriates and the South African Economy.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation) Johannesburg, 2019
Keywords: UCTD; Foreign Remuneration Exemption; Foreign tax credits; Double taxation treaties; Taxation--Law and legislation--South Africa; Income tax--South Africa; SDG-8: Decent work and economic growth